Communicology from the ‘portals’ perspective: a summative-schematic view - Puppel, Stanisław (Scripta Neophilologica Posnaniensia, 2019)
Communicology as a universal design is shown here as a phenomenon/process which can be accessed from a number of ‘portals’. Communicology as a design is defined as pluripotent and composed of five sphere-shaped components which contain universal and specific content. The content is assumed to embrace the totality of human communicative practices. The exposition of the content of the paper is presented in the form of summative schematics.